Regulatory mechanism of fermented wheat germ on lipid metabolism in hyperlipidemia rats via activation of AMPK pathway - MI,Shengquan (2022)
Abstract This article study the influences of fermented wheat germ on rats in terms of the blood glucose, insulin level, serum lipid level, cholesterol metabolism, triglyceride metabolism and enzyme activity on the basis of the high-fat rat model. High fat rats were fed for modeling, and then the serum and liver were collected after sacrifice. Total cholesterol (TC), triglyceride (TG), total superoxide dismutase (SOD), Superoxide dismutase (T-SOD), glutathione peroxidase (GSH-PX), Malonic dialdehyde (MDA), lecithin cholesterol acyltransferase (lecithin cholesterol), Acyltransferase (LCAT), LDL-C, blood glucose and insulin were measured. Fermented wheat germ can significantly increase the levels of insulin and blood glucose in high-fat rats. Fermented wheat germ for 60 days did not affect the levels of serum LDL-C and TG in high-fat rats, but could significantly reduce the level of serum TC. Fermented wheat germ for 60 days did not affect the activities of serum GSH-Px, T-SOD, LCAT and T-SOD, MDA and total lipase in high-fat rats, but it could significantly reduce the activity of serum MDA and increase the activity of GSH-PX in liver. Fermented wheat germ could reduce the protein expression of CYP7A1, induced p-AMPK protein expression, but had no effect on HMGR. Fermented wheat germ can significantly reduce the level of serum cholesterol in high-fat model rats by AMPK signaling pathway, and affect some cholesterol metabolism and triglyceride metabolism related enzyme activities to a certain extent.